Environ-economic analysis of high-temperature steam electrolysis for decentralized hydrogen production. (15th August 2022) - Lee, Jung Min; Lee, Sang-il; Kye, Deok Hoon; Park, Hyun Jae; Park, Woosung; Shin, Jeeyoung; Park, Kyungtae
Highlights: An integrated SOEC-VHTR plant is proposed for decentralized hydrogen production. The SOEC-VHTR plant is economical and sustainable with low CO2 emission. Process optimization and exergy, economic, and sensitivity analyses were performed. Different SOEC-VHTR configurations were studied considering carbon emission cost. Results confirm that the proposed plant is feasible as well as sustainable. Abstract: Hydrogen has attracted attention as a sustainable energy source that can replace fossil fuels because it does not emit CO2 during combustion. Water electrolysis can be used to generate "green hydrogen;" however, electricity prices determine the cost competitiveness of water electrolysis. Moreover, small-scale production is necessary owing to the difficulties in terms of the transport and storage of hydrogen. Thus, we propose a decentralized hydrogen production method using an integrated model of a solid oxide electrolyzer cell (SOEC) and a small modular reactor (SMR). A comparative study was also conducted for different configurations of the integrated model considering the carbon emission costs. The results indicate that when both electricity and heat are supplied from an SMR to the SOEC plant, the hydrogen production cost ranges from $5.02 to $7.60 per kg of H2, whereas the CO2 emission is the least at 0.36 kg per kg of H2 . Our findings suggest that the integrated model is both feasible and sustainable for decentralized hydrogen production.